2019
DOI: 10.3389/fmicb.2019.02689
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive Intestinal Peptide Deficiency Is Associated With Altered Gut Microbiota Communities in Male and Female C57BL/6 Mice

Abstract: Vasoactive intestinal peptide (VIP) is crucial for gastrointestinal tract (GIT) health. VIP sustains GIT homeostasis through maintenance of the intestinal epithelial barrier and acts as a potent anti-inflammatory mediator that contributes to gut bacterial tolerance. Based on these biological functions by VIP, we hypothesized that its deficiency would alter gut microbial ecology. To this end, fecal samples from male and female VIP+/+, VIP+/–, and VIP–/– littermates (n = 47) were collected and 16S rRNA sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 53 publications
(91 reference statements)
9
26
0
Order By: Relevance
“…VPAC1 KO fecal samples, which showed more substantial β-diversity changes compared to VPAC2 KO animals, also showed reductions in richness and α-diversity. Moreover, altered OTUs from VPAC1 fecal samples, including Bacteroides, Parabacteroides, Lactobacillus and Parasutterella, shared signi cant agreement to altered OTUs from VIP KO samples previously published 19 . In total, these data support that VIP receptor de ciency is associated with changes in gut microbiota ecology to different magnitudes and signaling mechanisms, highlighting their importance for gut health and homeostasis.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…VPAC1 KO fecal samples, which showed more substantial β-diversity changes compared to VPAC2 KO animals, also showed reductions in richness and α-diversity. Moreover, altered OTUs from VPAC1 fecal samples, including Bacteroides, Parabacteroides, Lactobacillus and Parasutterella, shared signi cant agreement to altered OTUs from VIP KO samples previously published 19 . In total, these data support that VIP receptor de ciency is associated with changes in gut microbiota ecology to different magnitudes and signaling mechanisms, highlighting their importance for gut health and homeostasis.…”
Section: Discussionsupporting
confidence: 78%
“…In this report, we show that genetic deletion of VPAC1 in homozygous mutant (KO) samples was associated with substantial changes in the gut microbiota composition compared to VPAC1 heterozygous (HET) or VPAC1 wild type (WT) littermates, irrespective of sex. Interestingly, out of the 94 differentially abundant OTUs in VPAC1 KO samples, there was agreement (≈63%) with statistically altered OTUs reported for VIP KO samples 19 . VPAC2 de ciency also resulted in differences compared to littermate controls, although the difference was much more subtle relative to the differences found in VPAC1-de cient mice.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…It has become apparent that the intestinal microbiota not only influences disease susceptibility 35 , 36 , but also affects inflammatory processes in general 50 , 51 . Several studies have shown direct involvement of neuropeptide systems in maintaining microbiome homeostasis 52 , 53 . The composition of commensal bacteria was unaffected by loss of GAL 3 R in healthy mice; therefore, increased disease susceptibility due to alterations to the microbiota in GAL 3 R-KO mice could be excluded.…”
Section: Discussionmentioning
confidence: 99%